Contextual interpretation of COVID-19 pandemic among public space users in Ibadan Metropolis, Oyo State, Nigeria: An ethnographic review - Mofeyisara Oluwatoyin Omobowale (Public Library of Science (PLoS), 2021)
The COVID-19 pandemic has affected all dimensions of lives and has become a social problem as it continues to spread widely through the continuous interactions of people in public spaces where they earn a living. Curbing the spread of COVID-19 requires restrictions in these public spaces, however, the compliance to these measures depends largely on the understanding and interpretations of COVID 19 by users of these public spaces. This study examined the contextual interpretations of public space users about COVID-19 prevention in Ibadan Metropolis, Oyo State. The study was a rapid ethnographic survey in selected public spaces (markets and commercial motor parks) in Ibadan metropolis. Data were collected through participant observation, key informant interviews (3 females; 3 males) and in-depth interviews (30) with, traders, head porters, clients/buyers and commercial vehicle drivers in these public spaces. Interviews conducted were transcribed, sorted into themes using Atlas-ti 7.5.7 and subjected to interpretive-content analysis. Findings revealed that some respondents felt COVID-19 was brought into Nigeria by rich frequent global voyagers, others felt it was through “uncultured” sexual life or wrath of God. Some also doubted the existence of the disease and many of the respondents perceived COVID-19 as a disease reported by the government or a political propaganda to siphon funds. The users of the public spaces in Ibadan Metropolis have variegated perception about the existence and severity of this rapidly spreading virus and this has grave implications for COVID-19 control in the State. Thus, regular interaction with public space users are essential for control efforts.